Recent trends in data science and soft computing : proceedings of the 3rd International Conference of Reliable Information and Communication Technology (IRICT 2018) /: proceedings of the 3rd International Conference of Reliable Information and Communication Technology (IRICT 2018). ([2019]) - Unknown
No abstract available